Transition excitation of a perfectly conducting cylinder by relativistic electron bunches - Balakirev, V.A.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2021)
Transition radiation of a relativistic electron bunch, which arises when it collides with the surface of an infinite perfectly conducting cylinder, is considered. The electron bunch moves perpendicular to the cylinder surface. Expressions for the field strength of electromagnetic radiation in the wave zone are obtained and investigated. Розглянуто перехідне випромінювання релятивістського електронного згусткa, що виникає при його зіткненні з поверхнею нескінченного ідеально провідного циліндра. Електронний згусток рухається перпендикулярно поверхні циліндра. Отримано і досліджено вирази для напруженості поля електромагнітного випромінювання в хвильової зоні. Рассмотрено переходное излучение релятивистского электронного сгустка, возникающее при его столкновении с поверхностью бесконечного идеально проводящего цилиндра. Электронный сгусток движется перпендикулярно поверхности цилиндра. Получены и исследованы выражения для напряженности поля электромагнитного излучения в волновой зоне.